1988
DOI: 10.1128/aac.32.12.1801
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of antimicrobial resistance in human fecal flora

Abstract: The frequency of resistance to seven different antimicrobial agents was examined in the aerobic gramnegative gut flora of over 600 individuals from hospitals, from laboratories where antibiotics were used, and from urban and rural communities. In a majority (62.5%) of fecal samples from people without a recent history of taking antibiotics, 10% or more of the total organisms were resistant to at least one of the antibiotics. In about 40% of the samples, resistance to more than one drug was present at this leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 17 publications
5
75
1
2
Order By: Relevance
“…However, this contrasts with other findings: examination of child day-care centres (DCC) [17] revealed substantially higher levels of trimethoprimresistant faecal flora (30%) amongst the children attending the centre than is prevalent in the general population (6%). Similarly, ampicillin-resistant faecal flora was reported as 70% in this particular population which again is substantially higher than corresponding levels identified in the healthy community (34 9 %) [9]. In the current study, approximately half the urban infants attended a child-minder in SOWETO, the equivalent of a child day-care centre, and yet the levels of resistance observed in this particular group are not noticeably higher than any other sub-group.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, this contrasts with other findings: examination of child day-care centres (DCC) [17] revealed substantially higher levels of trimethoprimresistant faecal flora (30%) amongst the children attending the centre than is prevalent in the general population (6%). Similarly, ampicillin-resistant faecal flora was reported as 70% in this particular population which again is substantially higher than corresponding levels identified in the healthy community (34 9 %) [9]. In the current study, approximately half the urban infants attended a child-minder in SOWETO, the equivalent of a child day-care centre, and yet the levels of resistance observed in this particular group are not noticeably higher than any other sub-group.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, the incidence of such resistance amongst the normal non-pathogenic 222 P. M. A. SHANAHAN AND OTHERS flora such as Escherichia coli of healthy individuals, in the absence of concurrent or recent antibiotic consumption, has been less extensively recorded [8][9][10][11]. The carriage of resistance determinants in these organisms may complicate treatment as the potential exists firstly, for their transfer to any invading pathogens and secondly, the resistant bacteria may cause an endogenous infection [12].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A linkage of fecal carriage of resistant bacteria to human antibiotic consumption has been demonstrated (Levy et al 1988;Barbosa and Levy 2000), and previous comparative studies have also revealed higher human antibiotic consumption in southern Europe than in Denmark (Fig. 2D, top and bottom left; Goossens et al 2005;Borg 2012), as well as higher proportions of resistant bacteria isolated from food-producing animals ( Table S1), and for which the time since introduction and animal usage approval information was available.…”
Section: Resultsmentioning
confidence: 99%
“…Alguns autores associam o consumo de alimentos vegetais como fontes de bactérias resistentes a antimicrobianos, principalmente da família Enterobacteriaceae, encontradas em amostras fecais de humanos saudáveis, mesmo na ausência de seleção por uso de terapia antimicrobiana [7,12].…”
unclassified